Psychological Well-being, Self-Efficacy, Social Support and Anxiety in Tuberculosis Patients During Covid-19 Pandemic - Saraswati, Dianing Ratri; Purwandari, Eny (Jurnal Kesehatan, 2023)
The Covid-19 pandemic that has affected several countries, including Indonesia, and is experienced by some people can also be experienced by tuberculosis patients. Tuberculosis patients themselves are double affected because Covid-19 and tuberculosis both attack the lungs, and these conditions can cause anxiety impacts for tuberculosis patients because they are more susceptible to contracting. This study aimed to examine the relationship between psychological well-being, self-efficacy, and social support with anxiety in tuberculosis patients during the Covid-19 pandemic. The method used is quantitative with linearity regression hypothesis analysis and respondents with the criteria of tuberculosis patients who were and still undergoing treatment during the Covid-19 pandemic, as many as 217 patients with a total of 121 male and 98 women respondents with an age range of 14 to 83 years. The study was conducted on some tuberculosis patients in Bandar Lampung. The results showed a relationship between psychological well-being, self-efficacy, and social support with anxiety in tuberculosis patients amid the Covid-19 pandemic with an r-value=0.510 and sig=0.000. Other results on categorization showed that the pressure of tuberculosis patients tends to be low, and psychological well-being, self-efficacy, and social support in tuberculosis patients tend to be medium level. The research is expected to improve psychological well-being and self-efficacy for tuberculosis patients, make others around tuberculosis patients pay more attention to patients, and provide social support to avoid anxiety during the Covid-19 pandemic.